Modelos de gestão do conhecimento: uma proposta de classificação - Zimetbaum, Sônia (2001)
This work presents a classification proposaI for modeIs of Administration of KnowIedge through the creation of three typoIogies, that makes easier the understanding of the main capitaIs of each modeI and the choice of the modeI adapted to impIant. A modeI is chosen and is justified through yours differentiate. It is anaIyzed the main capitaIs and authors of this modeI in relation to the retaiI sections and consultancy.